Analisis Web Smash Pada PT. Hitachi Channel Solutions Indonesia Jakarta Dengan Menggunakan Metode Webqual 4.0 - Normah, Normah; Udin, Komar; Rifai, Bakhtiar (Indonesian Journal on Software Engineering, 2024)
PT. Hitachi Channel Solutions Indonesia is a company engaged in the ATM sector since 2016 until now. The company has a website, namely web smash that this application is used for ticket making. The call center team or dispatcher will make when there is a report of a problem in the ATM machine by the client, the reporting is done by phone/email to the call center team. From the results of the report, it is summarized and made a ticket through web smash, the ticket will enter the ATM technician team to be checked, after the ATM problem has been fixed, the technician confirms to the call center team to close the ticket. In this study, it aims to conduct a web smash quality analyst where there are several obstacles found in web smash, namely related to sites that are accessed often have problems such as slow and lack of penetration between users so that development needs to be carried out to be able to improve the quality of web smash. From the results of the research using the webqual 4.0 method and SPSS Version 22 software, In the T test and F test, the significance result for the X3 variable (Service Penetration Quality) was found to be 0.000, the result was smaller than 0.05 which means that the variable greatly affects the quality of the web smash to improve the quality of the web smash for users, it is necessary to innovate the addition of features so that they can interact with each other and can facilitate the exchange of information